Protein synthesizing function and the functional state of liver of rats for the continuous cadmium and lead load - S. O. Slobodian; B. V. Gutyj (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
The aim of the study was to investigate the effect of Cadmium and Lead on the protein synthesis and function of the rat liver. The experiments were conducted in male rats of the Wistar line, weighing 200–220 g, of which 4 groups of animals were formed: 1) a control group – injected drinking water through a metal probe in a volume equivalent to the volume of an aqueous solution of Cd2+ salts and Pb2+; 2) experimental group 1 – animals were administered a 0.029% aqueous solution of cadmium chloride at a dose of 4.0 mg/kg; 3) experimental group 2 – animals were administered 16.6% aqueous lead acetate solution at a dose of 200 mg/kg; 4) experimental group 3 – animals were administered 16.6% aqueous lead acetate solution at a dose of 100 mg/kg and 0.029% aqueous cadmium chloride solution at a dose of 2.0 mg/kg. Throughout the experiment, rats were kept in a balanced diet containing all the necessary components, and animals were given drinking water, without restriction, from 0.2 liter glass bowls. The functional state of the liver of rats under the conditions of use of salts of heavy metals was investigated by the activity of aminotransferases. In long-term lead-cadmium loading in rats of the experimental groups, the functional state of the liver is characterized, which is characterized by an increase in the permeability of biological membranes of the cell membranes, which causes hyperfermentemia in blood serum, in particular aminotransferase (AST, ALT). The high activity of ALT and AST in the serum of rats under the influence of Cadmium and Lead indicates the destructive processes in the liver that cause an increase in the output of aminotransaminases from cell organelles in the blood of experimental animals. Thus, the results obtained indicate an increase in the destructive processes in the body of rats under lead-cadmium loading. Important diagnostic value for intoxication of different etiology is the determination of protein synthesis of liver function. An important indicator of liver protein synthesis is the level of total protein and its fractions in the serum. This indicator reflects the changes that occur in the body in different pathological conditions. When loaded with heavy metals in the body of rats inhibits the protein synthesis function of the liver, which is manifested by a decrease in total blood protein and albumin levels.